A Case of Primary Small-Cell Carcinoma of the Bladder - Ono, Ashita (Case Rep Oncol, 2016)
Primary small-cell carcinoma arising from the bladder (SmCCB) is uncommon. It differs from urothelial carcinoma (UC), the most common type of bladder cancer, with respect to its cell of origin, biology, and prognosis. Biologically, prostatic SmCCB is much more aggressive than UC, and the prognosis for cases with distant metastasis is especially poor. We report here a case of primary SmCCB (cT3bN1M0) treated with radical cystectomy.